PENGARUH HUKUM ADAT TERHADAP PRAKTIK PERNIKAHAN DIBAWAH UMUR DI MASYARAKAT GAYO - Sarwani, Novita (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
Occurs in some communities around the world, including Gayo’s community. Gayo community has a syntem of costomary law tha plays an important role in organizing community life, including the practice of marriage objectives of this research to analyze the underage unservice of the Gayo. The method used in this research is a qualitativeve approach with descriptive approach. Using interview, and document analysts are undernending underdomed practice in Gayo’s society.the results showed that the customary hammo in Gayo community has a strong influence on wending practices under umnur. The law provides legitimacy of underwriting practices with the grounds of maintaining the family’s honor, maintaining tradition, or avoiding social cinflicts. This study provides understanding of the causes of underage marriage practices in Gayo community, as well as the role of costomary law in this phenomenom